2013
DOI: 10.1007/s11517-013-1113-y
|View full text |Cite
|
Sign up to set email alerts
|

A metric for the stiffness of calcified aortic valves using a combined computational and experimental approach

Abstract: Calcific aortic valve disease is the most common heart valve disease. It is associated with a significant increase in cardiovascular morbidity and mortality and independently increases the cardiovascular risk. It is then important to develop parameters that can estimate the stiffness of the valve. Such parameters may contribute to early detection of the disease or track its progression and optimize the timing for therapy. In this study, we introduce a metric representing the stiffness of the native aortic calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The original non-stenotic Computer-Aided Design (CAD) model of the stenotic aortic valve was based on a previously published model [5,6]. The model is symmetric and includes three leaflets, three commissures, three sinuses, and three interleaflet triangles, which is consistent with Sutton et al's description of the normal aortic valve [7].…”
Section: Methodsmentioning
confidence: 78%
“…The original non-stenotic Computer-Aided Design (CAD) model of the stenotic aortic valve was based on a previously published model [5,6]. The model is symmetric and includes three leaflets, three commissures, three sinuses, and three interleaflet triangles, which is consistent with Sutton et al's description of the normal aortic valve [7].…”
Section: Methodsmentioning
confidence: 78%
“…Moreover, as mentioned above several recent cross-sectional biomechanical studies have demonstrated relationships between lumbopelvic control, kinematics and muscle activations to both increased pitch velocity and higher shoulder/elbow loads 1, 2, 21, 25-28, 30 . A lack of lumbopelvic control may lead to an inability of the pitcher to efficiently transfer energy from the legs to the hand, leading to excessive use of the shoulder, arm and wrist muscles to generate ball velocity.…”
Section: Discussionmentioning
confidence: 85%
“…We have recently published clinical case studies to accurately simulate MV dynamics of various pathologic conditions using our dynamic finite element protocol [37, 38]. It is anticipated that incorporation of realistic fluid-induced loading conditions on the valve cusps (e.g., physiologic 3D fluid-structure interaction simulation) will provide more accurate information pertaining to valvular dynamics [8, 19, 25, 27]. …”
Section: Discussionmentioning
confidence: 99%